2020
DOI: 10.1161/circulationaha.120.045765
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle–Mediated Delivery of Circular RNA SCMH1 Promotes Functional Recovery in Rodent and Nonhuman Primate Ischemic Stroke Models

Abstract: Background: Stroke is a leading cause of adult disability that can severely compromise patients' quality of life, yet no effective medication currently exists to accelerate rehabilitation. A variety of circular RNA (circRNAs) molecules are known to function in ischemic brain injury. Lentivirus-based expression systems have been widely used in basic studies of circRNAs, but safety issues with such delivery systems have limited exploration of potential therapeutic roles for circRNAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
186
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(188 citation statements)
references
References 68 publications
2
186
0
Order By: Relevance
“…A previous circRNAs microarray study in an established MCAO stroke model revealed that circUCK2 is one of the circRNAs downregulated during ischemic stroke. 27 Considering that circUCK2 plays a critical role in stroke, further experiments were needed to dissect the detailed mechanisms. In this study, we first detected the expression of circUCK2 in a murine ischemic stroke model (MCAO) using quantitative reverse transcription PCR (qRT-PCR), and the results showed that circUCK2 expression was decreased in the brain tissue of mice subjected to the MCAO model and in oxygen glucose deprivation (OGD)-induced HT-22 neurons ( Figures 1 A and 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous circRNAs microarray study in an established MCAO stroke model revealed that circUCK2 is one of the circRNAs downregulated during ischemic stroke. 27 Considering that circUCK2 plays a critical role in stroke, further experiments were needed to dissect the detailed mechanisms. In this study, we first detected the expression of circUCK2 in a murine ischemic stroke model (MCAO) using quantitative reverse transcription PCR (qRT-PCR), and the results showed that circUCK2 expression was decreased in the brain tissue of mice subjected to the MCAO model and in oxygen glucose deprivation (OGD)-induced HT-22 neurons ( Figures 1 A and 1B).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that circUCK2 was significantly downregulated in patients with ischemic stroke. 27 The overexpression of circUCK2 demonstrated substantial protective effects on neurons. As expected, our results elucidated the role of the circUCK2/miR-125b-5p/SIRT1 axis in stroke-associated neuronal injury and neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, plasma EVs originate from host cells mediate their mutual regulation locally or remotely, these EVs have cell type-specific biomolecules and could be exploited as predictive biomarkers for disease treatment [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] . The brain cell originated EVs could also be detected in CSF reflect the physiological and pathological changes taking place in the originated brain tissue [15] , [16] , [17] . Meanwhile, EVs encapsulate RNAs reflect the phenotype and functional states of their parent cells [18] .…”
Section: Introductionmentioning
confidence: 99%
“…CircHuR inhibits gastric cancer (GC) proliferation, invasion and metastasis by sequestering CCHC-type zinc finger nucleic acid binding protein (CNBP) from the human antigen R (HuR) promoter, thus downregulating HuR and repressing tumor [ 102 ]. Similarly, circSCMH1 delivered by EVs improves neuronal plasticity, and inhibits glial activation and immune cell infiltration post-stroke by sequestering methyl-CpG binding protein 2 (MeCP2) and compromising its role in transcriptional repression [ 103 ]. CircSamd4 [ 104 ] and autophagy-related circRNA (ACR) [ 105 ] also conform to this type.…”
Section: Circrna-protein Interactionsmentioning
confidence: 99%